Analysis of liner shipping networks and transshipment flows of potential hub ports in sub-Saharan Africa. (October 2018) - Kim, Hwa-Joong; Lam, Jasmine Siu Lee; Lee, Paul Tae-Woo
Abstract: Owing to growing economic growth in tandem with regional economic developments on the route connecting Asia and sub-Saharan Africa (SSA), several countries in the SSA region such as South Africa have been developing container ports. This paper analyzes potential trunk line routes and transshipment flows that could be captured by potential hub ports in the SSA region. To this end, integer programing models are developed to represent liner shipping networks in the SSA region and a wide variety of numerical experiments based on realistic data are conducted for the SSA-Europe and SSA-Asia trade routes. This paper draws various meaningful policy and managerial implications through scenario analyses such as the effects of network evolution, different vessel sizes and speeds, carbon taxes and insights in association with the 21st Century Maritime Silk Road initiated by China. Highlights: Analyze potential trunk line routes and transshipment flows that could be captured by hub ports in sub-Saharan Africa. Develop a model to determine container cargo flows, vessel routes, and the number of vessels per week. Conduct a variety of numerical experiments for the SSA-Europe and SSA-Asia trade routes. Draw practical implications through scenario analyses on effects of network evolution, different vessel sizes and speeds.